(untitled) (Communications in Computational Physics, 2018)
Phase separation of a two-dimensional van der Waals fluid subject to a gravitational force is studied by numerical simulations based on lattice Boltzmann methods implemented with a finite difference scheme. A growth exponent α=1 is measured in the direction of the external force.